Optimasi Ukuran KKG Sebagai Kemasan Transpor - Triyanto Hadisoemarto (Jurnal Kimia dan Kemasan, 1999)
Redesign of the existing transport corrugated box from its initial dimension of 504x404x202 mm consisting (5x4) primary packages of 1 liter liquid product, has been carried out to minimize the use of raw material, to maximize the pallet efficiency, and to improve its ability to withstand the laboratory scale of transportation simulation tests.The results indicate that all of those three purposes can already be achieved mainly by changing the formation of the primary packages in the box, i.e. from one stack (5x4) into two stacks 2(5x2). However, the best result is shown by the two stacks 2(4x2) of primary packages within the box having dimension of 404x205x395 mm.